STUDI KARAKTERISASI BATUAN BEKU DAN EVOLUSI MAGMA DI DAERAH RUWAI, PEGUNUNGAN SCHWANER, KABUPATEN LAMANDAU, KALIMANTAN TENGAH - , MUHAMMAD ILHAM N.A ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The study area is located at Ruwai, Lamandau District, Central Kalimantan Province. Based on the Regional Geology Map Sheet Tumbangmanjul (Margono, et al., 1995) is the location of the study is composed of Tonalite Sepauk Formation, Formation Sukadana Granite, and Volcanic Rock Formation Kerabai. However, based on the results of exploration activities conducted last few years (Ayson, 1997